1999
DOI: 10.1074/jbc.274.19.13375
|View full text |Cite
|
Sign up to set email alerts
|

Calcein as a Fluorescent Probe for Ferric Iron

Abstract: The recent use of calcein (CA) as a fluorescent probe for cellular iron has been shown to reflect the nutritional status of iron in mammalian cells (Breuer, W., Epsztejn, S., and Cabantchik, Z. I. (1995) J. Biol. Chem. 270, 24209 -24215). CA was claimed to be a chemosensor for iron(II), to measure the labile iron pool and the concentration of cellular free iron(II). We first study here the thermodynamic and kinetic properties of iron binding by CA. Chelation of a first iron(III) involves one aminodiacetic arm … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
60
0

Year Published

2001
2001
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 121 publications
(61 citation statements)
references
References 28 publications
1
60
0
Order By: Relevance
“…A very high affinity of phytate for Fe(III) and Al(III) has been previously suggested by several workers [12,51]. A ''free Fe(III)'' treatment, similar to that used for divalent cations in relation to EDTA, showed that InsP 6 has an affinity for Fe(III) in the range of that of the multidentate chelator calcein (further discussed below) [52]. We detected only 1:1 complexes with the trivalent cations.…”
Section: Interaction With Trivalent Cationsmentioning
confidence: 63%
See 2 more Smart Citations
“…A very high affinity of phytate for Fe(III) and Al(III) has been previously suggested by several workers [12,51]. A ''free Fe(III)'' treatment, similar to that used for divalent cations in relation to EDTA, showed that InsP 6 has an affinity for Fe(III) in the range of that of the multidentate chelator calcein (further discussed below) [52]. We detected only 1:1 complexes with the trivalent cations.…”
Section: Interaction With Trivalent Cationsmentioning
confidence: 63%
“…The fluorescent iron chelator, calcein, is an experimental tool regarded as likely to help resolve this issue [52,60]. We reasoned that if InsP 6 -complexed iron existed in cells, it would necessarily be as Fe(III), for two related reasons.…”
Section: Biological Predictions In Relation To Fe(iii)/fe(ii)mentioning
confidence: 99%
See 1 more Smart Citation
“…The fluorescence of calcein (CA) is quenched upon iron binding; the amount of CA-bound iron is subsequently determined by the amount of CA fluorescence recovered upon addition of a competing, membrane-permeant iron chelator like BIP or SIH. Although there is some controversy about the specificity of CA for Fe 2ϩ versus Fe 3ϩ (45), the data clearly show that chelators like BIP and SIH are Fe 2ϩ -specific indicating that in the cell CA is chelating Fe 2ϩ . This chelatable Fe 2ϩ constitutes ϳ20% of the total iron in both mammalian and yeast cells in culture (30,35).…”
Section: Bipyridyl Treatment Does Not Inhibit Ribonucleotide Reductasmentioning
confidence: 91%
“…Although significant contributions to the development of spectroscopic sensing for Fe 3+ have been made over the last few decades [14][15][16][17], there have been relatively few fluorescent probes for Fe 3+ which showed "off-on" signal. It might be due to its paramagnetic nature which leads to fluorescence quenching.…”
Section: Introductionmentioning
confidence: 99%